A Time-Series Analysis of Economic Growth in the Context of Indian Economy - Asma Hashim; Syed Mohammad Faisal; Ahmad Khalid Khan (Integrated Journal for Research in Arts and Humanities, 2022)
India has a sizable and successful consumer class, which is critical given that household consumption accounts for 60% of GDP. Total market value is calculated by adding the monetary or market values of all final goods and services produced inside a nation's borders. Additionally, the gross domestic product at market value (GDP at market value) may be employed to reflect this total market value. Total domestic production is defined in terms of GDP to assess the economy's health. GDP is computed on a quarterly or yearly basis, depending on the state of the economy at the moment. Human capital is a country's most important natural resource, and it must be used appropriately and acknowledged to accomplish long-term economic goals sustainably. India is the world's second-most populated nation, with 1.3 billion people behind China. According to the World Bank, India's global influence has grown in lockstep with its consistent economic success. Compared to wealthier nations, emerging countries have several obstacles, including a lack of infrastructure and a low per capita income. Another issue that has to be addressed is the growth of rural economic systems. According to some experts, India's current economic instability will culminate in an unprecedented economic boom, which they believe has already begun.